PROSES PEMBENTUKAN KONFORMITAS DALAM PENDAMPINGAN ANAK YANG BERHADAPAN DENGAN HUKUM DI KOTA TANJUNGPINANG - Herdany, Venny; Arieta, Siti; Suryaningsih (PT. Intelek Cendikiawan Nusantara, 2024)
Conformity is the behavior or actions of individuals in adjusting the positive norms and values applied in society. One of the crimes committed by children is theft. Children involved in criminal activity basically lack self-control. Children in conflict with the law are children aged 12 to 18 years who are in conflict with the law. Children who are paroled are returned to their parents and reintegrated into society. The Tanjung Unggat area is one of the places where children who commit crimes live. Children who receive prison sentences and have received parole will be returned to their parents and return to the community. So that the return of children dealing with the law experiences readjustment to the environment. Robert K. Merton defines conformity as the adjustment of individuals in heeding to society, with conformity through normative, agreement, obedience, cohesiveness and informational means.This research uses a descriptive type qualitative approach. The results of the research on the process of obedience of children accustomed to doing 5-time prayers because when they are in prison if they do not pray they will get a witness through this pressure the child becomes obedient. Children also make agreements by obeying the rules of limiting night out. Through the process of choosing to.